Risk factors for possible REM sleep behavior disorders: A community-based study in Beijing. (20th October 2020) - Zhang, Hui; Gu, Zhuqin; Yao, Chun; Cai, Yanning; Li, Yuan; Mao, Wei; Xu, Erhe; Postuma, Ronald B.; Chan, Piu
Abstract : Objective: To explore the risk factors for idiopathic REM sleep behavior disorder (RBD) in a community population in Beijing. Methods: Participants aged 55 years and above were recruited from the Beijing Longitudinal Study on Aging II cohort. We identified individuals with possible RBD (pRBD) using the validated RBD Questionnaire–Hong Kong in 2010. A series of environmental, lifestyle, and other potential risk factors were assessed via standardized questionnaires in 2009. Multivariable logistic regression analysis was performed to investigate the association between the studied factors and pRBD. Results: Of 7, 225 participants who were free of parkinsonism and dementia, 219 (3.0%) individuals were considered as having pRBD. Participants with pRBD reported more nonmotor and motor symptoms of Parkinson disease (PD) with adjusted odds ratios (ORs) ranging from 1.10 to 4.40. Participants with pRBD were more likely to report a family history of parkinsonism or dementia (OR 3.03, 95% confidence interval [CI] 1.23–7.46). There was a significant association between pRBD and self-reported hyperlipidemia (OR 1.51, 95% CI 1.09–2.10), ever smoking (OR 1.79, 95% CI 1.20–2.65), prior carbon monoxide (CO) poisoning (OR 2.30, 95% CI 1.39–3.83), and nonoccupational exposure to pesticides (OR 2.21, 95% CI 1.40–3.50). Conclusion: Our study replicated previously reported associations between pRBD and hyperlipidemia, smoking, pesticide exposure, and several prodromal PD symptoms. We also found previously unreported links with a positive family history of parkinsonism or dementia and CO poisoning. Risk factor profiles for pRBD partially resemble those defined for PD, but also differ in distinct ways.